2013
DOI: 10.1016/j.jep.2012.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive effect of Lecythis pisonis Camb. (Lecythidaceae) in models of acute pain in mice

Abstract: These results indicate the antinociceptive effect of Lecythis pisonis leaves and suggest that this effect may be related to opioid pathway, K+ATP channels, and L-arginine-nitric oxide modulation. Furthermore, these data support the ethnomedical use of this plant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…[38][39][40] Another possible mechanism of the anti-inflammatory and antinociceptive effects may be the inhibition of cyclooxygenase activities, just as the aspirin. 41 Cyclooxygenase catalyzes the biosynthesis of prostaglandins from arachidonic acid. 42 Again the mechanism of antinociceptive effects may be through the inhibition of pain perception, impulse transmission and/or elevation of pain threshold in the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40] Another possible mechanism of the anti-inflammatory and antinociceptive effects may be the inhibition of cyclooxygenase activities, just as the aspirin. 41 Cyclooxygenase catalyzes the biosynthesis of prostaglandins from arachidonic acid. 42 Again the mechanism of antinociceptive effects may be through the inhibition of pain perception, impulse transmission and/or elevation of pain threshold in the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…)31, a non-selective opioid receptor antagonist, prior to the administration of either morphine (10 mg/kg) or DHC (10 mg/kg). Then formalin (5%, 25 μl) was injected into the paw 15 min after the administration of morphine or DHC in the established formalin pain model.…”
Section: Methodsmentioning
confidence: 99%
“…erefore, it was deduced that the levels of L-glutamate and NO increased. A previous study indicated that acetic acid-induced abdominal writhing was associated with NO production and the glutamatergic system [23]. Writhing may happen when ulcers cause abdominal pain, and glutamate was the major excitatory neurotransmitter involved in nociceptive signal transmission.…”
Section: Discussionmentioning
confidence: 99%